Pengaruh Edukasi Terhadap Pengetahuan Dan Sikap Mengenai Pemutih Kulit Badan Pada Siswi SMK Widya Yahya Gading Rejo - Regita Aulia Safitri; Riza Dwiningrum; Mida Pratiwi; Yenny Marthalena (Journal of Innovative and Creativity, 2025)
The large number of dangerous cosmetic products on the market and the low level of knowledge among teenagers regarding skin whitening products mean that the use of skin whitening products requires an understanding of the ingredients used in a product and an awareness of the risks of harmful effects. The aim of this study is to analyze the effect of education on knowledge and attitudes regarding skin whitening products among female students at SMK Widya Yahya Gading Rejo. The method used in this study is a quantitative method employing a quasi-experimental non-equivalent control group design. The study sample consists of 103 respondents from SMK Widya Yahya Gading Rejo, divided into two groups: the treatment group and the control group. The results of the study showed that the percentage of knowledge in the treatment group before education (pre-test) was 82.7% (good category) and after education (post-test) was 94.2% (good category). The percentage of attitudes in the treatment group before education (pre-test) was 98.1% (good category) and after education (post-test) was 100% (good category). The conclusion of this study is that there is an effect of education on knowledge and attitudes regarding skin whitening products among female students at SMK Widya Yahya Gading Rejo with a p-value >0.001. It is hoped that this research will provide information and knowledge to the public and institutions, as well as serve as a scientific reference, particularly in the field of pharmacy.